Comparing Fin Intramedullary Nailing with Standard Locked Intramedullary Nailing in the Fixation of Humeral Shaft Fractures - Adesina, Stephen Adosope; Anipole, Olalekan Akeem; Eyesan, Samuel Uwale; Ikem, Innocent Chiedu; Akinwumi, Akinsola Idowu; Bamigboye, Philip Oluyemi; Oyewusi, Oluwafemi Oyewole (Nigerian Journal of Orthopaedics and Trauma, 2020)
Background: Standard interlocking intramedullary nailing of the humeral shaft fractures has its attending complications such as difficulty in locking the nail distally and associated nerve injuries. Aim: To compare the rate of fracture healing, functional outcome and complication rate between SIGN standard locked intramedullary nail (SSLIN) and SIGN intramedullary fin nail (SIFN) in the management of humeral shaft fractures. Method: This is a retrospective comparative study comprising of patients who were treated with either SSLIN or SIFN for humeral shaft fractures. They were followed up until full activities of daily living was achieved. Data collected were processed with SPSS. Comparisons were made between the two groups using student t-test for the continuous variables and Chi-square for the categorical variables. Results: Forty-three patients with humeral shaft fracture were included in this study. Thirty-one of them constituted the SSLIN group while 12 of them constituted the SIFN group. At 6 weeks, radiographic evidence of fracture healing was seen in 64.5% and 58.3% of the patients in the SSLIN and SIFN groups respectively and by the third month, 96.8% and 100% of the patients respectively had achieved radiographic evidence of fracture healing. The differences were not significantly different. There was also no significant difference in the findings from the comparative assessment of functional outcomes in both groups. Conclusion: SIFN compared favorably with the SSLIN in terms of rate of fracture healing and resumption of functional activities. SIFN is therefore encouraged to be used for humeral shaft fractures.